Impact of Thermal Boundary Resistance on Thermoelectric Effects of the Blade-Type Phase-Change Random Access Memory Device - Lian, Xiaojuan; Fu, Jinke; Gao, Zhixuan; Ren, Wang; Wan, Xiang; Ren, Qingying; Wen, Jing; Yang, Cihui; Liu, Xiaoyan; Wang, Lei (Frontiers in Materials, 2022)
Phase-change random access memory (PCRAM) is widely regarded as one of the most promising candidates to replace Flash memory as the next generation of non-volatile memories due to its high-speed and low-power consumption characteristics. Recent advent of the blade-type PCRAM with low programming current merit further confirms its prospects. The thermoelectric effects existing inside the PCRAM devices have always been an important factor that determines the phase-transformation kinetics due to a fact that it allows PCRAM to have electric polarity dependent characteristics. However, the potential physics governing the thermoelectric effects for blade-type PCRAM device still remains vague. We establish a three-dimensional (3D) electro-thermal and phase-transformation model to study the influences of thermal boundary resistance (TBR) and device scaling on the thermoelectric effects of the blade-type PCRAM during its ‘RESET’ operation. Our research shows that the presence of TBR significantly improves the electric polarity-dependent characteristics of the blade-type PCRAM, and such polarity-dependent characteristic is found immune to the scaling of the device. It is therefore possible to optimize the thermoelectric effects of the blade-type PCRAM through appropriately tailoring the TBR parameters, thus further lowering resulting power consumption.